Ruby and grub - Burlingham Abi (New York; Little Bee Books, 2015)
Ruby loves her messy dog named Grub, who is a bit of a trouble maker, but she is dismayed when her mother has had enough of his antics and sends the dog to live with relatives
Keywords: Picture books collection